Hip Muscle Strength and Functional Deficits in Patients with Avascular Necrosis of Femoral Head and Hip Replacement - Mukkamala, Neha; Mehta, Ananya; Parmar, Lata; Kumar, G P (Research Highlights in Disease and Health Research Vol. 3, 2023)
Avascular necrosis (AVN) of femoral head causes pain, joint stiffness, muscle wasting and physical disability, whereas hip replacement, commonly done for AVN reduces pain, improves mobility, strength and physical function. This study aimed to assess the strength and functional deficits due to AVN preoperatively and postoperatively after hip replacement. This was an observational study. Hip muscle strength of all subjects with AVN of femoral head scheduled for hip replacement was taken by modified sphygmomanometer. Self reported Harris hip score and TUG test were also taken for these subjects. All subjects underwent physiotherapy during hospital stay. Again all outcome measures were taken post hip replacement on on the day of discharge. Healthy adults were recruited for measuring hip muscle strength. In this study, 32 subjects, 16 with AVN and 16 healthy adults were recruited. 28-males and 8-females. Mean age-36.88 years in both groups. Isometric muscle strength preoperatively in AVN subjects of hip flexors-76.75±50.67 mm of Hg, abductors-54.56±30.74 and extensor apparatus 75.38±37.32 was significantly reduced (p<0.001) compared to healthy adults,(hip flexors-188.42±15.69, abductors 112.67±21.66 and extensor apparatus-171.71±25.60). Postoperatively strength of hip flexors-93.12±52.58, abductors-63.62±33.74 and extensor apparatus-88.94±41.22 was reduced compared to healthy adults. Postop significant improvement (p<0.05) seen at discharge in strength compared to preoperative values. Conclusion: Muscle strength of hip muscles, both in subjects with AVN preoperatively and post replacement, was significantly reduced compared to normals. Postoperatively improvement was seen at discharge in strength compared to preoperative values.